2019
DOI: 10.1073/pnas.1819689116
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial viruses exhibit diurnal rhythms during infection

Abstract: As an adaptation to the daily light–dark (diel) cycle, cyanobacteria exhibit diurnal rhythms of gene expression and cell cycle. The light–dark cycle also affects the life cycle of viruses (cyanophages) that infect the unicellular picocyanobacteriaProchlorococcusandSynechococcus, which are the major primary producers in the oceans. For example, the adsorption of some cyanophages to the host cells depends on light, and the burst sizes of cyanophages are positively correlated to the length of light exposure durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(85 citation statements)
references
References 44 publications
(84 reference statements)
14
71
0
Order By: Relevance
“…In contrast, P-SSP7 dynamics were better explained by light-driven host growth rate. Our results corroborate the observations of [37], adding mechanistic evidences of light-driven Prochlorococcus infection dynamics. The failure of P-HM2 to adsorb to MED4 in the dark indicates that adsorption could be directly modulated by light, as suggested by [36].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In contrast, P-SSP7 dynamics were better explained by light-driven host growth rate. Our results corroborate the observations of [37], adding mechanistic evidences of light-driven Prochlorococcus infection dynamics. The failure of P-HM2 to adsorb to MED4 in the dark indicates that adsorption could be directly modulated by light, as suggested by [36].…”
Section: Discussionsupporting
confidence: 90%
“…As in [37]: "Axenic Prochlorococcus strains were grown in Port Shelter (Hong Kong) seawater-based Pro99 medium [57]. Batch cultures were incubated at 23 • C in continuous light (25 µmol quanta m −2 s −1 ) or a 14h light:10h dark cycle (35 µmol quanta m −2 s −1 in the light period).…”
Section: Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is unclear how the temporal expression of phage Fd changes the flux of nutrients during the cyclical lifecycle of cyanobacteria. Recent studies have revealed that cyanophage gene expression and replication is diurnally linked to host replication, with both processes occurring during the afternoonevening period when light intensity is high (18,78,79). Additionally, phage transcripts drop at night and when photosystem is compromised (18).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that cyanophage gene expression and replication is diurnally linked to host replication, with both processes occurring during the afternoonevening period when light intensity is high (18,78,79). Additionally, phage transcripts drop at night and when photosystem is compromised (18). Despite these advances, we don't know what feedback loops govern expression of phage genes in infected cells, especially photosynthesis-related genes derived from host homologs.…”
Section: Discussionmentioning
confidence: 99%